Geomechanics of Australian open cut coal mining - Simmons, JV (Slope Stability 2020: Proceedings of the 2020 International Symposium on Slope Stability in Open Pit Mining and Civil Engineering, 2020)
Australian black coal and brown coal mining is an important contributor to the Australian economy. The intent of this paper is to provide concise reference information to geotechnical practitioners. Geology of coals, coal measures rocks, overburdens, and groundwater are described. Mining operations for the black coal and brown coal industries are very different. Both are outlined to provide a context for geotechnical characterisation that covers rank, coal materials, virgin and pre-existing stress states, and data gathering. Geotechnical models and parameters are described separately for the black coal and brown coal sectors. Information is provided regarding material and mass strength, deformability, degradation and weathering, hydraulic conductivity, gas desorption and outburst, and waste dumping. An overview of analytical tools is provided for defect mapping, slope stability, and deformation and groundwater pressure modelling. Discussion of geotechnical aspects of final post-mining landforms is also provided.
Keywords: open cut coal mining